CULTURE AS NATIONAL IDENTITY IN PREPARING YOUNG GENERATION FOR THE INDUSTRIAL REVOLUTION 4.0 - Rafsanjani, Wildan Akbar Hashemi; Yuana, Sunu Tri; Navalina, Vania Kirana Fitria (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2021)
Culture is a way to develop a life that has social elements that are comprehensive to form character. This study aims to examine that local wisdom is one of the national resilience to create further generations in the face of the industrial revolution 4.0 so that the nation's identity is maintained. The research method used is qualitative methods with interviews about the 4.0 industrial revolution, the research location is in Jakarta. Industrial revolution 4.0 is influenced by technological progress or changes. The results obtained by the younger generation prepare for a national identity that looks beautiful with the existing culture.